Corpus linguistics for English for academic purposes - Viana, Vander; O'Boyle, Aisling (London ; New York: Routledge, 2021)
"Corpus Linguistics for English for Academic Purposes (EAP) shows how corpus analyses can enhance students', practitioners' and researchers' knowledge of academic language"--
Includes appendices and index.
Keywords: Corpora (Linguistics); English language -- Study and teaching (Higher) -- Foreign speakers; English language -- Rhetoric -- Study and teaching (Higher)